A fast-curing conductive silver glue and its production process
By using nanospherical silver powder and silver-coated graphene oxide composite technology in conductive silver glue, the problem of uncontrollable conductivity in the rapid curing process is solved, and the uniformity of conductive properties and the reduction of volume resistivity is achieved.
Patent Information
- Application Number
- CN202410905075.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-07-08
AI Technical Summary
In the rapidly curing conductive silver glue system, nano-level silver fillers are unevenly melted during the heating and curing process, resulting in uncontrollable conductive networks and affecting the uniformity of the product's conductive performance.
Nanosphere silver powder and silver-coated graphene oxide are used as conductive fillers to form a stable conductive network by regulating particle size distribution and island-like deposition of the silver-coated layer.
The relatively stable structure of the conductive network during the rapid curing process is realized, ensuring the uniformity of the conductive properties and low volume resistivity of the product.
Smart Images

Figure BDA0004931800930000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of packaging materials, and more specifically, relates to a fast-curing conductive silver glue and a production process thereof. Background Art
[0002] The main components of conductive silver glue are: polymer resin, curing agent, silver powder, additives and other components. Resins are more common in epoxy resin, acrylic resin, silicone resin and thermoplastic resin. Among them, epoxy resin is the most widely used in electronic conductive glue due to its excellent thermal properties, high adhesion and small shrinkage. The conductive silver glue based on epoxy resin usually has a curing temperature between 100-180℃, and curing at different temperatures will have a greater impact on the conductivity. Epoxy resin usually uses amine curing agents to form a curing system. Traditional conductive silver glue epoxy resin curing agents include imidazole, dicyandiamide, acid anhydride, etc. The more commonly used acid anhydride curing agents, such as methyl hexahydrophthalic anhydride, have the characteristics of low viscosity, good stability, wide sources, and low prices. Acid anhydride curing agents usually need to add a certain amount of tertiary amine as a catalyst. Under the catalysis of tertiary amine, they can be quickly cured at 150℃ and generally have a longer service life.
[0003] The conductive filler of conductive adhesive is mainly silver powder. The silver powder used in conductive adhesive is mainly classified into spherical, flake, granular and fibrous silver powder according to different shapes. Among them, flake silver powder is the most widely used. However, according to experimental measurements, adding appropriate spherical silver powder to flake silver powder will help to improve conductivity and reduce the amount of silver powder used. As we all know, the melting point of nano silver powder can be reduced to 140-160℃, while the curing temperature of conductive adhesive is generally above 150℃. Therefore, during the curing process of conductive adhesive, nano silver powder or silver wire can be melted to form metal welding with flake silver powder to increase conductivity and greatly reduce the volume resistivity of conductive adhesive. However, at this stage, nano silver powder or silver wire is extremely expensive and its stability is not particularly ideal, so its actual use is subject to certain restrictions. In particular, for the fast-curing conductive silver adhesive system, nano silver powder or silver wire cannot be fully melted and form a relatively complete conductive network, which makes it difficult to ensure the uniformity of volume resistivity in different parts of the product. Summary of the invention
[0004] The technical problem to be solved by the present invention is that for a fast-curing conductive silver paste system, although adding conductive fillers with different morphologies can improve the conductive performance to a certain extent, the nano-scale silver filler will melt during the reheating and curing process. The melting of silver particles with different morphologies will cause the conductive network to become uncontrollable, especially during the fast curing process. The heat is unevenly distributed in the surface and inner layers of the colloid, which will aggravate the inconsistency of melting in different parts, and ultimately lead to the problem that the conductive performance of the product cannot be uniformly guaranteed. A fast-curing conductive silver paste and a production process thereof are provided.
[0005] The purpose of the present invention is to provide a fast-curing conductive silver paste.
[0006] Another object of the present invention is to provide a production process for rapidly curing conductive silver paste.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A fast-curing conductive silver paste comprises the following raw materials in parts by weight: 35-40 parts of base resin, 8-10 parts of curing agent, 65-70 parts of conductive filler, 3-5 parts of auxiliary agent, and 0.3-0.5 parts of catalyst;
[0009] Wherein, the base resin is liquid bisphenol F type resin;
[0010] The conductive filler comprises the following filler composition in parts by weight: 20-30 parts of nano-spherical silver powder and 60-70 parts of silver-coated graphene oxide;
[0011] The sphericity of the nano-spherical silver powder is 8.8-9.0;
[0012] The D50 of the nano-spherical silver powder is 20-30nm;
[0013] The D50 of the silver-coated graphene oxide is 100-200 μm;
[0014] The catalyst is selected from any one of dimethylaminophenol and 2-ethyl-4-methylimidazole.
[0015] Two silver conductive fillers with different morphologies are used for compounding, specifically, nano-spherical silver powder and silver-coated graphene oxide. The difference in particle size distribution between the two will lead to different degrees of difficulty in melting during the heating and curing process. Specifically, the smaller nano-spherical silver powder is easier to melt, and then forms a conductive network with the silver coated on the surface of graphene oxide. Graphene oxide itself has conductivity and will not melt during the heating and curing process, so that the overall structure of the conductive network is relatively stable during the rapid curing process. In addition, thanks to the excellent thermal conductivity efficiency of graphene oxide, during the heating and curing process, the temperature of different regions inside the system can be quickly balanced, which is conducive to the formation of a relatively more uniform conductive network in different parts.
[0016] The inventors found that the use of spherical nano-silver powder can form an effective filling between it and the layered graphene oxide. In addition, the particle size between the graphene oxide and the silver powder is regulated so that the graphene oxide is significantly larger than the silver powder. In this way, the spherical nano-silver powder can be adsorbed and fixed on the surface of the graphene oxide to avoid excessive agglomeration of itself. The uniform adsorption on the surface of the graphene oxide will cause the graphene oxide to melt during the rapid heat transfer process, thereby forming a structurally stable conductive network with the graphene oxide as the binding site.
[0017] Preferably, the silver-coated graphene oxide comprises a graphene oxide matrix and a silver coating layer coated on the surface of the graphene oxide matrix; the mass of the silver coating layer is 0.65-0.75 times the mass of the graphene oxide matrix.
[0018] Preferably, in the silver-coated graphene oxide, the silver coating layer is coated in an island shape on the surface of the graphene oxide substrate.
[0019] By further regulating the amount of silver coating on the surface of graphene oxide, if the coating amount is too little, it is difficult to form a complete conductive network structure with nano silver powder. If the coating amount is too much, the density of graphene oxide will increase significantly, and it is easy to settle in the epoxy resin system, thereby reducing the dispersion stability of the overall conductive filler, and finally the conductive performance of the product is uneven.
[0020] In addition, the silver on the corresponding graphene oxide surface is coated in an island shape, which will expose part of the structure of the graphene oxide surface, thus making it easier for the nano silver powder to be adsorbed on the surface.
[0021] Preferably, the curing agent is selected from any one of phthalic anhydride, methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride.
[0022] The combination of anhydride curing agents and catalysts can effectively accelerate the curing rate of epoxy resin systems and achieve the purpose of rapid curing.
[0023] Preferably, the auxiliary agent includes a dispersant and a coupling agent;
[0024] Wherein, the amount of the dispersant is 2.5-3 times the mass of the coupling agent;
[0025] The dispersant is selected from any one of oleamide, oleic acid, stearic acid monoglyceride, tristearic acid glyceride, and polyethylene wax;
[0026] The coupling agent is selected from aluminate coupling agent; the aluminate coupling agent is selected from any one of aluminate coupling agent SG-Al821, aluminate coupling agent DL-411AF, and aluminate coupling agent DL-411DF.
[0027] A production process for fast curing conductive silver glue, the specific process steps include:
[0028] Weigh each component according to the raw material formula;
[0029] First, the base resin, conductive filler, additive and catalyst are stirred and mixed evenly, and then the curing agent is added. After continuing to stir and mix evenly, the material is discharged to obtain the fast-curing conductive silver glue.
[0030] Preferably, the specific process steps also include:
[0031] After mixing graphene oxide and glucose solution, hydrothermally reacting, filtering and drying after the reaction is completed, to obtain pretreated graphene oxide;
[0032] The pretreated graphene oxide and the silver nitrate solution are mixed, ultrasonically dispersed evenly, and then a sodium hydroxide solution is added. After heating and stirring for reaction, the mixture is filtered, washed, dried, ground, and sieved to obtain the silver-coated graphene oxide.
[0033] Preferably, the specific process steps also include:
[0034] The graphene oxide and the glucose solution with a mass fraction of 10% are mixed in a mass ratio of 1:(8-10), and the mixture is subjected to a hydrothermal reaction for 3-5 hours at a temperature of 120-130° C. and a pressure of 1.2-1.4 MPa. After the reaction is completed, the mixture is filtered and dried to obtain the pretreated graphene oxide;
[0035] The pretreated graphene oxide and the silver nitrate solution with a mass fraction of 8-10% are mixed in a mass ratio of 1: (8-10), and then ultrasonically dispersed evenly. Then, a sodium hydroxide solution with a concentration of 4 mol / L is added, and after heating and stirring for reaction, the mixture is filtered, washed, dried, ground, and sieved to obtain the silver-coated graphene oxide.
[0036] Preferably, the specific process steps also include:
[0037] The graphene oxide and the glucose solution with a mass fraction of 10% are mixed in a mass ratio of 1:(8-10), and the mixture is subjected to a hydrothermal reaction for 3-5 hours at a temperature of 120-130° C. and a pressure of 1.2-1.4 MPa. After the reaction is completed, the mixture is filtered and dried to obtain the pretreated graphene oxide;
[0038] The pretreated graphene oxide and a silver nitrate solution with a mass fraction of 8-10% are mixed in a mass ratio of 1: (8-10), and then ultrasonically dispersed uniformly. Then, a 4 mol / L sodium hydroxide solution with a concentration of 0.6-0.8 times the mass of the silver nitrate solution and a 10% ammonia solution with a mass fraction of 0.1-0.2 times the mass of the silver nitrate solution are added. After heating and stirring for reaction, the mixture is filtered, washed and dried, ground, and sieved to obtain silver-coated graphene oxide.
[0039] By using glucose solution and graphene oxide for hydrothermal reaction, the graphene oxide surface is endowed with corresponding functional groups for the island-like deposition of the silver coating layer. The deposition amount on the graphene oxide surface is controlled by adjusting the amount of silver nitrate and the preparation process parameters. DETAILED DESCRIPTION
[0040] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0041] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0042] Example 1
[0043] According to the weight percentage, 35 parts of base resin, 8 parts of curing agent, 65 parts of conductive filler, 3 parts of auxiliary agent, and 0.3 parts of catalyst were weighed;
[0044] Wherein, the base resin is liquid bisphenol F type resin;
[0045] The conductive filler comprises the following filler composition in parts by weight: 20 parts of nano-spherical silver powder and 60 parts of silver-coated graphene oxide;
[0046] The sphericity of the nano-spherical silver powder is 8.8;
[0047] The D50 of the nano-spherical silver powder is 20 nm;
[0048] The D50 of the silver-coated graphene oxide is 100 μm;
[0049] The catalyst is selected from dimethylaminophenol;
[0050] First, the base resin, conductive filler, additive and catalyst are stirred and mixed with a stirrer at a speed of 800r / min for 4h, and then the curing agent is added, and the stirring and mixing is continued for 30min, and then the material is discharged to obtain a fast-curing conductive silver glue;
[0051] Wherein, the preparation steps of the silver-coated graphene oxide are:
[0052] Graphene oxide and a 10% glucose solution were mixed in a mass ratio of 1:8 and poured into a hydrothermal reactor. The mixture was subjected to a hydrothermal reaction at a temperature of 120° C. and a pressure of 1.2 MPa for 3 h. After the reaction was completed, the mixture was filtered, the filter cake was collected, and the filter cake was vacuum dried to obtain pretreated graphene oxide.
[0053] The pretreated graphene oxide and the silver nitrate solution with a mass fraction of 8% were mixed in a mass ratio of 1:8, and ultrasonically dispersed for 60 minutes at an ultrasonic frequency of 120kHz, and then 0.6 times the mass of the silver nitrate solution and a sodium hydroxide solution with a concentration of 4 mol / L, and 0.1 times the mass of the silver nitrate solution and ammonia water with a mass fraction of 10% were added, and the mixture was heated and stirred at a temperature of 75°C and a stirring speed of 600r / min for 3 hours, and then filtered to collect the filter cake, and the filter cake was washed with deionized water until the washing liquid was neutral, and then the washed filter cake was transferred to an oven for vacuum drying, and then ground and sieved to obtain silver-coated graphene oxide;
[0054] The mass of the silver coating layer is 0.65 times the mass of the graphene oxide matrix; and the silver coating layer is coated on the surface of the graphene oxide in an island shape.
[0055] Example 2
[0056] According to the weight percentage, 38 parts of base resin, 9 parts of curing agent, 68 parts of conductive filler, 4 parts of auxiliary agent, and 0.4 parts of catalyst were weighed;
[0057] Wherein, the base resin is liquid bisphenol F type resin;
[0058] The conductive filler comprises the following filler composition in parts by weight: 25 parts of nano-spherical silver powder and 65 parts of silver-coated graphene oxide;
[0059] The sphericity of the nano-spherical silver powder is 8.9;
[0060] The D50 of the nano-spherical silver powder is 26 nm;
[0061] The D50 of the silver-coated graphene oxide is 170 μm;
[0062] The catalyst is selected from 2-ethyl-4-methylimidazole;
[0063] First, the base resin, conductive filler, additive and catalyst are stirred and mixed with a stirrer at a speed of 800r / min for 4h, and then the curing agent is added, and the stirring and mixing is continued for 30min, and then the material is discharged to obtain a fast-curing conductive silver glue;
[0064] Wherein, the preparation steps of the silver-coated graphene oxide are:
[0065] Graphene oxide and a 10% glucose solution were mixed in a mass ratio of 1:9 and poured into a hydrothermal reactor. The mixture was subjected to a hydrothermal reaction for 4 hours at a temperature of 125°C and a pressure of 1.3 MPa. After the reaction was completed, the mixture was filtered, the filter cake was collected, and the filter cake was vacuum dried to obtain pretreated graphene oxide.
[0066] The pretreated graphene oxide and a silver nitrate solution with a mass fraction of 9% were mixed in a mass ratio of 1:9, and ultrasonically dispersed for 70 minutes at an ultrasonic frequency of 130kHz, and then a sodium hydroxide solution with a concentration of 4 mol / L and a mass fraction of 10% ammonia water with a mass fraction of 0.15 times the mass of the silver nitrate solution were added, and heated and stirred for reaction for 4 hours at a temperature of 78°C and a stirring speed of 600r / min, and then filtered to collect the filter cake, and the filter cake was washed with deionized water until the washing liquid was neutral, and then the washed filter cake was transferred to an oven for vacuum drying, and then ground and sieved to obtain silver-coated graphene oxide;
[0067] The mass of the silver coating layer is 0.69 times the mass of the graphene oxide matrix; and the silver coating layer is coated on the surface of the graphene oxide in an island shape.
[0068] Example 3
[0069] According to the weight percentage, weigh 40 parts of base resin, 10 parts of curing agent, 70 parts of conductive filler, 5 parts of auxiliary agent, and 0.5 parts of catalyst;
[0070] Wherein, the base resin is liquid bisphenol F type resin;
[0071] The conductive filler comprises the following filler composition in parts by weight: 30 parts of nano-spherical silver powder and 70 parts of silver-coated graphene oxide;
[0072] The sphericity of the nano-spherical silver powder is 9.0;
[0073] The D50 of the nano-spherical silver powder is 30 nm;
[0074] The D50 of the silver-coated graphene oxide is 100-200 μm;
[0075] The catalyst is selected from dimethylaminophenol;
[0076] First, the base resin, conductive filler, additive and catalyst are stirred and mixed with a stirrer at a speed of 800r / min for 4h, and then the curing agent is added, and the stirring and mixing is continued for 30min, and then the material is discharged to obtain a fast-curing conductive silver glue;
[0077] Wherein, the preparation steps of the silver-coated graphene oxide are:
[0078] Graphene oxide and a 10% glucose solution were mixed in a mass ratio of 1:10 and poured into a hydrothermal reactor. The mixture was subjected to a hydrothermal reaction at a temperature of 130° C. and a pressure of 1.4 MPa for 5 h. After the reaction was completed, the mixture was filtered, the filter cake was collected, and the filter cake was vacuum dried to obtain pretreated graphene oxide.
[0079] The pretreated graphene oxide and a silver nitrate solution with a mass fraction of 10% are mixed in a mass ratio of 1:10, and ultrasonically dispersed for 80 minutes at an ultrasonic frequency of 140kHz, and then a sodium hydroxide solution with a concentration of 4 mol / L and a mass fraction of 0.8 times the mass of the silver nitrate solution and ammonia water with a mass fraction of 10% and a mass fraction of 0.2 times the mass of the silver nitrate solution are added, and heated and stirred for reaction for 5 hours at a temperature of 85°C and a stirring speed of 600r / min, and then filtered to collect the filter cake, and the filter cake is washed with deionized water until the washing liquid is neutral, and then the washed filter cake is transferred to an oven for vacuum drying, and then ground and sieved to obtain silver-coated graphene oxide;
[0080] The mass of the silver coating layer is 0.75 times the mass of the graphene oxide matrix; and the silver coating layer is coated on the surface of the graphene oxide in an island shape.
[0081] Example 4
[0082] Compared with Example 1, the present example is different in that no glucose is added and the other conditions remain unchanged.
[0083] Example 5
[0084] The present embodiment is different from the embodiment 1 in that the silver nitrate solution uses a silver nitrate solution with a mass fraction of 15%, so that the mass of the silver coating layer on the surface of the graphene oxide substrate is 0.78 times the mass of the graphene oxide substrate.
[0085] Comparative Example 1
[0086] The difference between this comparative example and Example 1 is that the silver-coated graphene oxide is replaced by flaky silver powder of equal mass, and the D50 of the flaky silver powder is 100 μm, and the other conditions remain unchanged.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 1 is that the silver powder with a D50 of 20 μm of the same mass is used to replace the nano silver powder, and the other conditions remain unchanged.
[0089] The performance tests were performed on the products obtained in Examples 1-5 and Comparative Examples 1-2. The specific test methods and test results are as follows:
[0090] Shear strength test:
[0091] According to GB / T 7124-2008, transfer the bonded iron sheets into a 150°C oven for heating and curing for 30 minutes, take out the patch, and after cooling to room temperature, perform a shear strength test;
[0092] Volume resistivity:
[0093] Test volume resistivity according to GB / T 1410-2006;
[0094] The relevant test results are shown in Table 1:
[0095] Table 1: Product performance test results
[0096]
[0097]
[0098] It can be seen from the test results in Table 1 that the product obtained by the present invention not only has excellent bonding performance, but also has low volume resistivity.
[0099] According to the above-mentioned volume resistivity test method, the conductive silver paste in different areas of the patch surface is sampled accordingly. Five samples are taken from the same group of samples. The maximum and minimum values in the same group of test results are compared. The difference between the two is regarded as the deviation of the reorganized sample. The relevant test results are shown in Table 2.
[0100] Table 2: Bias test results
[0101] Volume resistivity deviation / Ω·m Example 1 <![CDATA[0.03×10 -6 ]]> Example 2 <![CDATA[0.02×10 -6 ]]> Example 3 <![CDATA[0.02×10 -6 ]]> Example 4 <![CDATA[0.06×10 -6 ]]> Example 5 <![CDATA[0.07×10 -6 ]]> Comparative Example 1 <![CDATA[0.22×10 -6 ]]> Comparative Example 2 <![CDATA[0.19×10 -6 ]]>
[0102] It can be seen from the test results in Table 2 that after the product obtained by the present invention is cured, the volume resistivity of different parts is relatively uniform.
[0103] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A fast curing conductive silver paste, characterized in that: The method comprises the following raw materials in parts by weight: 35-40 parts of base resin, 8-10 parts of curing agent, 65-70 parts of conductive filler, 3-5 parts of auxiliary agent, and 0.3-0.5 parts of catalyst; The matrix resin is a liquid bisphenol F type resin; the conductive filler comprises the following filler components in parts by weight: 20-30 parts of nano-spherical silver powder and 60-70 parts of silver-coated graphene oxide; the sphericity of the nano-spherical silver powder is 8.8-9.0, and the D50 is 20-30nm; the D50 of the silver-coated graphene oxide is 100-200μm; The catalyst is selected from any one of dimethylaminophenol or 2-ethyl-4-methylimidazole; The silver-coated graphene oxide comprises a graphene oxide matrix and a silver coating layer coated on the surface of the graphene oxide matrix; the mass of the silver coating layer is 0.65-0.75 times the mass of the graphene oxide matrix; The preparation steps of silver-coated graphene oxide include: Graphene oxide and 10% glucose solution are mixed in a mass ratio of 1:(8-10), and then subjected to hydrothermal reaction for 3-5 hours at a temperature of 120-130°C and a pressure of 1.2-1.4MPa. After the reaction is completed, the mixture is filtered and dried to obtain pretreated graphene oxide. The pretreated graphene oxide and a silver nitrate solution with a mass fraction of 8-10% are mixed in a mass ratio of 1: (8-10), and then ultrasonically dispersed evenly. Then, a 4 mol / L sodium hydroxide solution with a concentration of 0.6-0.8 times the mass of the silver nitrate solution and a 10% ammonia solution with a mass fraction of 0.1-0.2 times the mass of the silver nitrate solution are added. After heating and stirring for reaction, the mixture is filtered, washed and dried, ground and sieved to obtain silver-coated graphene oxide.
2. The fast curing conductive silver paste according to claim 1, characterized in that: In the silver-coated graphene oxide, the silver coating layer is coated in an island shape on the surface of the graphene oxide substrate.
3. The fast curing conductive silver paste according to claim 1, characterized in that: The curing agent is selected from any one of phthalic anhydride, methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride.
4. The fast curing conductive silver paste according to claim 1, characterized in that: The auxiliary agent includes a dispersant and a coupling agent; Wherein, the amount of the dispersant is 2.5-3 times the mass of the coupling agent; The dispersant is selected from any one of oleamide, oleic acid, stearic acid monoglyceride, tristearic acid glyceride, and polyethylene wax; The coupling agent is selected from aluminate coupling agent; the aluminate coupling agent is selected from any one of aluminate coupling agent SG-Al821, aluminate coupling agent DL-411AF, and aluminate coupling agent DL-411DF.
5. A production process of the fast curing conductive silver paste according to any one of claims 1 to 4, characterized in that: The specific process steps include: Weigh each component according to the raw material formula; First, the base resin, conductive filler, additive and catalyst are stirred and mixed evenly, and then the curing agent is added. After continuing to stir and mix evenly, the material is discharged to obtain the fast-curing conductive silver glue.
Citation Information
Patent Citations
Method for efficiently preparing silver nano particle-graphene three-dimensional composite structure
CN104148663A
Preparation method of epoxy conductive adhesive
CN111171772A